MANAJEMEN KINERJA PENDIDIKAN ISLAM - Mohammad Khamami Zadih; Kalimatun Naimah; Muhammad Al Faruq; Liyang Putri Ayu (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2024)
Entering the era of globalization, Islamic educational institutions have a big responsibility to answer various community demands, especially in improving the quality of education by improving the quality of human resources within them. Performance management is one alternative that can be used by Islamic education institutions to improve the quality of human resources within them to achieve their goals according to institutional market demands. Performance management is a process of creating an understanding of what should be, and how to achieve it and an approach to managing people to increase the likelihood of achieving work-related outcomes. Performance management is carried out on an ongoing basis for an institution, individual and process using a systems approach, namely work analysis, cause analysis and an intervention system which will produce management changes towards achieving better results. Through performance management applied to Islamic educational institutions, it is hoped that creating quality that is climate and atmosphere oriented (quality culture) and has a competitive advantage with other educational institutions.Keywords: Performance management, Competition